Employer provided training in Austria: Productivity, wages and wage inequality - René Böheim; Nicole Schneeweis; Florian Wakolbinger (Johannes Kepler University of Linz, Department of Economics, 2009)
We use data on Austrian firms and employees to estimate the effects of employer-provided training on productivity, wages, and the inequality of wages within firms. While the average amount spent on employer-provided training is low in general, we find a robust positive elasticity of training on productivity of about 0.04. In-house training is more effective than external courses, and language, administrative and personal skills courses are more effective than sales training and IT-courses. We find a significant relationship between training and wages, the coefficient is about 0.05. We find no significant effect of training on the inequality of wages within firms.
Keywords: D21; J24; 330; employer-provided training; productivity; wages; Betriebliches Bildungsmanagement; Arbeitsproduktivität; Lohndifferenzierung; Qualifikation; Österreich